2003
DOI: 10.1562/0031-8655(2003)077<0431:tctote>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cells That Overexpress the Epidermal Growth Factor Receptor with Polyethylene Glycolated BPD Verteporfin Photosensitizer Immunoconjugates¶

Abstract: Photoimmunotherapy was introduced two decades ago but has been studied infrequently in vivo and is virtually untested clinically. Progress has been limited because high-quality, well-characterized photosensitizer immunoconjugates (PICs) have been difficult to make. Here, we describe the development of an innovative conjugation method for producing water-soluble PICs that are free of insoluble aggregates and free of unacceptable amounts of noncovalently associated photosensitizer impurities. The method exploits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
132
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 92 publications
(140 citation statements)
references
References 27 publications
8
132
0
Order By: Relevance
“…S4). Furthermore, previous in vitro studies have shown that Cet-BPD is highly selective to cancer cells overexpressing EGFR surface molecules with 20-fold less accumulation in low EGFR-expressing cells (35). Hence, the tumor selectivity achieved by Cet-BPD is due to tumor-targeted activation.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…S4). Furthermore, previous in vitro studies have shown that Cet-BPD is highly selective to cancer cells overexpressing EGFR surface molecules with 20-fold less accumulation in low EGFR-expressing cells (35). Hence, the tumor selectivity achieved by Cet-BPD is due to tumor-targeted activation.…”
Section: Resultsmentioning
confidence: 96%
“…This quenching phenomenon increases the tumor specificity when optimally designed; however, excess BPD loading results in the loss of cancer cell-specific delivery. In a series of chemical synthesis and in vitro cell culture studies, we previously identified an optimal conjugation ratio of approximately seven BPD molecules per mAb molecule, Cet-BPD(1:7), as a strongly quenched (sevenfold) and cancer cell-specific construct (35) that retains the biological activity of cetuximab (36). These in vitro studies suggest that, like cetuximab, Cet-BPD is trafficked to lysosomes as part of the EGFR internalization and degradation pathway where more than one-half of the Cet-BPD immunoconjugates release BPD resulting in dequenching and activation of both BPD phototoxicity and fluorescence emission in cell culture (37).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously verteporfin PICs consisting of an EGFR (epidermal growth factor recpetor-1) recognizing MAb C225 were found on a per mole basis to be significantly less phototoxic than free visudyne. 16 It is known that in the presence of aqueous buffers such as PBS, hydrophobic photosensitizers have a tendency to aggregate with consequent photophysical quenching. 38 The singlet oxygen data therefore strongly suggest that the PPa molecules are spatially arranged on the scFv such that there is less adverse photophysical interaction between PS molecules.…”
Section: Discussionmentioning
confidence: 99%
“…14 Photosensitizers conjugated to whole antibodies can target a range of cancers 12 or pathogens 15 ; however, experiences so far has shown that many technical problems exist in coupling high numbers of PS to whole antibodies. These include impaired antibody binding, reduced solubility [16][17][18][19] and unfavorable pharmacokinetics due to the resulting high molecular weight of such photoimmunoconjugates (PICs). Some researchers have tried using carrier moieties such as branched carbohydrate or polylysine chains, which are in turn linked to the antibody.…”
mentioning
confidence: 99%